Mechanical Thrombectomy Outcomes With and Without Intravenous Thrombolysis in Stroke Patients: A Meta-Analysis. Issue 9 (September 2017) - Mistry, Eva A.; Mistry, Akshitkumar M.; Nakawah, Mohammad Obadah; Chitale, Rohan V.; James, Robert F.; Volpi, John J.; Fusco, Matthew R.
Abstract : Background and Purpose—: Whether prior intravenous thrombolysis provides any additional benefits to the patients undergoing mechanical thrombectomy for large vessel, acute ischemic stroke remains unclear. Methods—: We conducted a meta-analysis of 13 studies obtained through PubMed and EMBASE database searches to determine whether functional outcome (modified Rankin Scale) at 90 days, successful recanalization rate, and symptomatic intracerebral hemorrhage rate differed between patients who underwent mechanical thrombectomy with (MT+IVT) and without (MT−IVT) pre-treatment with intravenous thrombolysis. Results—: MT+IVT patients compared with MT−IVT patients had better functional outcomes (modified Rankin Scale score, 0–2; summary odds ratio [OR], 1.27 [95% confidence interval (CI), 1.05–1.55]; P =0.02; n=1769/1174), lower mortality (OR, 0.71 [95% CI, 0.55–0.91]; P =0.006; n=1774/1202), and higher rate of successful recanalization (OR, 1.46 [95% CI, 1.09–1.96]; P =0.01; n=1652/1216) without having increased odds of symptomatic intracerebral hemorrhage (OR, 1.11 [95% CI, 0.69–1.77]; P =0.67; n=1471/1143). A greater number of MT+IVT patients required ⩽2 passes with a neurothrombectomy device to achieve successful recanalization (OR, 2.06 [95% CI, 1.37–3.10]; P =0.0005; n=316/231). Conclusions—: Our results demonstrated that MT+IVT patients had better functional outcomes, lower mortality, higher rate of successful recanalization, requiring lower number of device passes, and equal odds of symptomatic intracerebral hemorrhage compared with MT−IVT patients. The results support the current guidelines of offering intravenous thrombolysis to eligible patients even if they are being considered for mechanical thrombectomy. Because the data are compiled from studies where the 2 groups differed based on eligibility for intravenous thrombolysis, randomized trials are necessary to accurately evaluate the added value of intravenous thrombolysis in patients treated with mechanical thrombectomy. Abstract : Supplemental Digital Content is available in the text.